2018
DOI: 10.1186/s13019-018-0739-0
|View full text |Cite
|
Sign up to set email alerts
|

Positive impact of retrograde autologous priming in adult patients undergoing cardiac surgery: a randomized clinical trial

Abstract: BackgroundAdult cardiac surgery with extracorporeal circulation is known to be associated with increased risk of blood transfusion leading to adverse outcomes. Procedures like retrograde autologous priming (RAP) may reduce these negative side effects. This randomized prospective study was initiated to assess whether RAP using specifically designed RAP bag (Terumo) has immediate effects on patient outcome.MethodsOne hundred eighteen adults undergoing elective CABG or elective aortic valve replacement were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 27 publications
0
29
1
2
Order By: Relevance
“…A recent study that has shown AP is a cost-effective method that reduces RBC transfusion, with a minimum displaced volume of 350 mL. 8 In this study, survey respondents reported that AP was used 87.1% versus 72.4% in LT and HT groups, respectively, with more than double the number of centers in the HT group not using AP compared to the LT. When AP was used, the average volumes were approximately 190 mL greater in the LT then HT patients.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A recent study that has shown AP is a cost-effective method that reduces RBC transfusion, with a minimum displaced volume of 350 mL. 8 In this study, survey respondents reported that AP was used 87.1% versus 72.4% in LT and HT groups, respectively, with more than double the number of centers in the HT group not using AP compared to the LT. When AP was used, the average volumes were approximately 190 mL greater in the LT then HT patients.…”
Section: Discussionmentioning
confidence: 70%
“…The use of AP and ANH during cardiac surgery are especially attractive blood management interventions since they reduce both hemodilution and RBC transfusion. 8,17 We have shown that the combination of these two modalities are volume dependent with the greatest benefit seen when ANH volumes exceeded 350 mL. 17 Furthermore, there was a gender-specific effect on Hct, with women showing greater drops in Hct at similar removed volumes than men.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hemodilution resulting in low hematocrit levels during CPB is known to be responsible for impaired hemostasis. Retrograde autologous priming (RAP) is a technique that may reduce hemodilution and subsequently reduce transfusion requirement and possibly bleeding ( 40 ). RAP is not used at our institution and, therefore, we cannot comment on the effect of RAP on the decision to use albumin postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…La aplicación de medidas de recebado sanguíneo del circuito basan su beneficio en la reducción de la agresión hemodilucional al paciente por medio del desplazamiento de la solución cristaloide que compone el cebado inicial del circuito con sangre autóloga del paciente, reduciendo así la transfusión de concentrados de hematíes y las complicaciones perioperatorias 257 . El Purgado Autólogo Retrógrado (RAP), así como el Recebado Anterógrado Hemático (HAR) cuentan con el máximo nivel de recomendación y evidencia para reducir la exposición a hemoderivados y sus complicaciones en el postoperatorio temprano y hasta el alta 250,252 . 87.…”
Section: La Aplicación De Miecc Se Recomienda Como Me-unclassified